Numerical Study of Wave- and Current-Induced Oscillatory Seabed Response near a Fully Buried Subsea Pipeline - Lunliang Duan; Meiling Fan; Duoyin Wang; Caixia Meng; Lei Xing (Advances in Civil Engineering)
To investigate the wave- and current-induced seabed response near a fully buried subsea pipeline, a two-dimensional coupled model for fluid-seabed-pipeline interaction (FSPI-2D) is developed within the framework of COMSOL multiphysics. Different from previous studies, both the wave-current interaction and the nonlinear pipeline-soil contacts are considered in the present model. In this paper, Biot’s consolidation mode is used to govern the fluid-induced seabed response, and combined Reynolds averaged Navier–Stokes (RANS) equation with the k-ε turbulence model is employed to simulate the fluid propagation. Meanwhile, the pipeline is treated as a linear elasticity. Firstly, the effectiveness of the new model is verified by laboratory experiments from previous reports. Then, the numerical model is employed to examine the effects of nonlinear pipeline-seabed contacts and fluid characteristics on the seabed response around the structure. Finally, the momentary liquefaction near the fully buried pipeline is studied based on the 2D coupled model.